La inmigración que nos cogió desprevenidos: el vaivén de las políticas de extranjería - Ospina Sánchez, Gloria Inés (UNISCI Discussion Papers, 2007)
This article analyzes the evolution of policies and legislation on immigration in Spain, from the transition to democracy until now. As a conclusion, some suggestions for the countries that send or receive migration flows are offered.